The experience of effort in ADHD: a scoping review - Wagner, Danika; Mason, Samantha G.; Eastwood, John D. (Frontiers in Psychology, 2024)
Background Mental effort plays a critical role in regulating cognition. However, the experience of mental effort may differ for individuals with Attention-Deficit/Hyperactivity Disorder (ADHD), a disorder for which sustained mental effort ‘avoidance’ or ‘dislike’ is a criterion in the DSM. We conducted a scoping review to characterize the literature on the experiences of effort in ADHD. Methods This systematic scoping review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) Extension for Scoping Reviews and Joanna Briggs Methodology. PsycINFO (OVID), PsycINFO (ProQuest) and PubMed were searched for studies published in English before February 14, 2023. Studies must have included an ADHD population or a measure of ADHD symptomatology, in addition to a self-report measure of the experience of effort or the use of an effort preference paradigm. Two researchers reviewed all abstracts, and one researcher reviewed full-text articles. Results Only 12 studies met the inclusion criteria. Several gaps and inconsistencies in the research were identified in terms of method, definitions of effort, measurements of ADHD, and sample characteristics. Moreover, the pattern of results on the experience of effort was mixed. Conclusion Despite its diagnostic and conceptual significance, the experience of mental effort in ADHD is not well studied. Critical gaps were identified in the existing literature. A three-facet conceptualization of effort is proposed–specifically, task-elicited effort, volitionally exerted effort, and the affect associated with engaging in effort – to guide future explorations of the experience of effort in ADHD.